Robots in American popular culture - Carper, Steve (McFarland and Company, Inc., 2019)
They are invincible warriors of steel, silky-skinned enticers, stealers of jobs and lovable goofball sidekicks. Legions of robots and androids star in the dream factories of Hollywood and leer on pulp magazine covers, instantly recognizable icons of American popular culture. For two centuries, we have been told tales of encounters with creatures stronger, faster and smarter than ourselves, making us wonder who would win in a battle between machine and human. This book examines society's introduction to robots and androids such as Robby and Rosie, Elecktro and Sparko, Data, WALL-E, C-3PO and the Terminator, particularly before and after World War II when the power of technology exploded. Learn how robots evolved with the times and then eventually caught up with and surpassed them. -- Back cover.
Keywords: Robots -- In popular culture.; Robots in literature.; Robots in motion pictures.; Popular Culture.; SOCIAL SCIENCE.; Robots in popular culture; Robots in literature; Robots in motion pictures